Isolation, Purification and In Vitro Characterization of a Newly Isolated Alkalophilic Phytase Produced by the Halophile Cobetia marina Strain 439 for Use as Animal Food Supplement - Ivanka Boyadzhieva; Kaloyan Berberov; Nikolina Atanasova; Nikolay Krumov; Lyudmila Kabaivanova (Fermentation)
Economic development increases and brings about issues such as the secure supply of food in a sustainable way. Phytases are enzymes catalyzing phytate hydrolysis to release phosphorus in an inorganic form. Animal feeds could be supplemented with bacterial phytases to increase their phosphorus and micronutrients bioavailability. To the best of our knowledge, this is the first report on the purification and characterization of an alkalophilic phytase from Cobetia marina. The purified newly isolated phytase from the halophilic Cobetia marina strain 439 appears to be appropriate for use as an additive in food and feed processing. Its molecular weight was determined to be 43 kDa by gel filtration and 40 kDa by SDS–polyacrylamide gel electrophoresis. The purified enzyme had maximum activity at pH 8.0 and 45 °C, while at 70 °C, it was 80% and about 50% at 80 °C for 40 min, showing its thermostability. Enzyme activity was retained at a broad pH range from 6.5 to 9.0. The half-life of the phytase of 15 min at pH 10 and 30 min at pH 4.0 was registered. The enzyme was proven to be with high substrate specificity. In addition, the purified phytase showed strong proteolytic tolerance against trypsin and pepsin. The pH profile, its thermostability, and proteolytic tolerance of the studied phytase as a halophilic bacterial product determine it as a unique candidate for application in agriculture, food, and feed industries.